Skrining “GEMULEK” (Gigi, Mulut, dan KEK) pada Perempuan Usia Subur dalam Pencegahan Stunting - Girsang, Bina Melvia; Sitohang, Ance Marintan D; Elfira, Eqlima; Sofyanti, Ervina (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
Prevention of dental and oral health problems in pregnant women can be done by increasing knowledge and changing the behavior of pregnant women. The target audience for this community service activity are women of childbearing age, pregnant women, and posyandu cadres. The partner in this community service is the head of the posyandu cadre in Ujung Rambung village. The partner's problem lies in the emergence of dental and oral health problems and KEK during pregnancy. Screening activities for women of childbearing age in Ujung Rambung village include 12 components of dental and mouth screening, as well as upper arm circumference screening as an observation of nutritional status, and also detects the average age of women of childbearing age who attend as participants. Based on the results of the screening tabulation, it was found that 61.5% of the activity participants had cavities, and 73.1% had tartar. This condition is a condition that is at risk of developing tooth and mouth infections. Apart from that, in a number of other problems, 26.9% found cases of bleeding teeth when brushing their teeth, and they often experienced food stuck in their teeth (53.8%). In the study of measuring upper arm circumference (LILA) as a monitoring of nutritional status and chronic energy deficiency (KEK), the average LILA was 30.08 cm. This was also followed by monitoring of reproductive age with an average age of 32.7 years. Nutritional status and maternal health before, during and after pregnancy affect the early growth and development of children, starting from the womb. Gingivitis of pregnancy is inflammation of the gums experienced during pregnancy. Oral screening and the incidence of CED are important components that can be complied with during the early trimester of pregnancy.